1995
DOI: 10.1002/nur.4770180609
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiologic factors contributing to functional performance in people with COPD: Are there gender differences?

Abstract: The purpose of this study was to compare the functional performance profiles of men and women with chronic obstructive pulmonary disease, describe the extent to which physiologic impairment, physical symptoms, and psychosocial resources contribute in a cumulative manner to performance, and outline the extent to which these contributions differ across gender. Secondary data analyses were employed. Although women (n = 45) reported more functional difficulty than men (n = 44) in 9 of 12 Sickness Impact Profile ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Moreover, female patients with symptoms had a lower QOL in a number of areas. The importance of current symptoms for patients' QOL and health status has already been established in previous studies Leidy & Traver, 1995;Wirnsberger, De Vries, Breteler et al, 1998). However, from the present study it became clear that a patient's gender is crucial in determining QOL.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Moreover, female patients with symptoms had a lower QOL in a number of areas. The importance of current symptoms for patients' QOL and health status has already been established in previous studies Leidy & Traver, 1995;Wirnsberger, De Vries, Breteler et al, 1998). However, from the present study it became clear that a patient's gender is crucial in determining QOL.…”
Section: Discussionsupporting
confidence: 49%
“…In the investigation by Williams and Bury (1989), male COPD patients reported more problems in the area of work, while female COPD patients had more problems in the area of domestic responsibilities. Finally, research by Leidy and Traver (1995) indicated that somatic symptoms predicted health status in female COPD patients only.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, many patients have a realistic attitude towards life and they view changes as part of life. 17 Families of home oxygen therapy patients were significantly more flexible and slightly more stable than families of inpatients. Family functioning was good in both groups.…”
Section: Discussionmentioning
confidence: 98%
“…7,16,17 Families of both home oxygen patients and inpatients functioned well on the dimension of mutuality. Families of both patient groups had a sense of emotional closeness.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 However other researchers found no difference in the level of fatigue between men and women. 11,20 …”
Section: Relevant Literaturementioning
confidence: 93%